The GATT, quantitative restrictions, and the balance of payments - Frank, Isaiah (Washington D.C. : The World Bank, 1987)
The purpose of this paper is to examine the rationale for the present GATT roles on QRs; convey an indication of the extent of resort to the balance of payments exception to the rules; evaluate the roles of the GATT and the IMF in monitoring the exception; assess the appropriateness of the exception under present circumstances; and propose a way of dealing with the problem in the context of the current multilateral trade negotiations
Discussion paper
osc 30/01/2019
Ref
Keywords: Tariff preferences; Free trade